CARDIOPROTECTIVE POTENTIAL OF QUERCETIN AGAINST DIESEL OR PETROL EXHAUST NANOPARTICLE INDUCED TOXICITY: A PROSPECTIVE IN VITRO PHARMACOLOGICAL STUDY IN H9C2 CELLS - DURGA, MOHAN; DEVASENA, THIYAGARAJAN (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Phytochemicals are known to elicit potential antioxidant activity. This study examined the cardioprotective effects of quercetin against oxidative damage to rat cardiomyocyte cells (H9c2) after treatment with Diesel Exhaust Nanoparticles (DEPs) or Petrol Exhaust Nanoparticles (PEPs). Methods: Cardiomyocyte cells were exposed to DEPs or PEPs alone and in a combination with quercetin for 24 h. Results: Results showed that quercetin had no lethal effect on H9c2 cells up to a concentration of 1.0 μg/ml. Exposure to DEPs (4.0 μg/ml) or PEPs (10.0 μg/ml) induced cytotoxicity, oxidative stress, and inflammation (p<0.05). It also provoked lipid peroxidation by an increase in MDA and a decrease in SOD activity and glutathione activity (p<0.05). Simultaneous addition of quercetin restored these parameters to near normal. Conclusion: These results thus specify that quercetin plays a protective role in cardiac cells exposed to DEPs and PEPs.